, Niech zginą nałogi mięsno-wódczano-tytuniowo-modne”. Programy i idee polskich wegetarian XIX i początku XX stulecia - Pasieka, Paweł (Studia Europaea Gnesnensia, 2018)
The article presents an analysis of the ideas and platforms developed by the first Polish vegetarians in the latter half of the 19th and in the early 20th century. The views of the following authors are considered: Konstanty Moes-Oskragiełło, Józef Drzewiecki, Janisław Jastrzębowski and Rajmund Jankowski. I draw attention to three basic features: anthropocentrism, eclecticism and a somewhat informal culture.